Convergence analysis for a system of equilibrium problems and a countable family of relatively quasi-nonexpansive mappings in banach spaces - Suthep Suantai (2018)
We introduce a new hybrid iterative scheme for finding a common element in the solutions set of a system of equilibrium problems and the common fixed points set of an infinitely countable family of relatively quasi-nonexpansive mappings in the framework of Banach spaces. We prove the strong convergence theorem by the shrinking projection method. In addition, the results obtained in this paper can be applied to a system of variational inequality problems and to a system of convex minimization problems in a Banach space. © 2010 Prasit Cholamjiak and Suthep Suantai.